HARMONISASI IMPLEMENTASI QANUN KHALWAT DENGAN QANUN PEMBINAAN KEHIDUPAN ADAT DAN ISTIADAT (Suatu Penelitian di Kabupaten Bireuen) - Azzubaili, Taqwaddin Husen, Muzakkir Abubakar. (Jurnal Ilmu Hukum, 2014)
Abstract: The research shows that there is normative harmonization in settling the case in Aceh, in solving the case by the Customary Trial or Islamic Local Law, in its implementation by the people, its synchronization as the process solved by the trial is a part of its jurisdiction and also the law is also has its jurisdiction that can be solved by the Islamic court. It is recommended that the customary law enforcers should solve the case hence in punishing does not cause and courage a new dispute;, hence it is not causing the perspective that the customary law is not fair. The beholder is providing the report regarding the handling of the cases to parties that have the authority.; hence there is no overlapping and the law is not only for one side interest in solving the case regarding the violation of Islamic local law. Keywords: Harmonization, Implementation, Customs. Abstrak: Penelitian menggambarkan bahwa adanya harmonisasi normatif dan sosiologis lembaga-lembaga yang menyelesaikan kasus khalwat di Aceh Tujuan akhirnya adalah sama yaitu menciptakan kedamaian dan ketentraman dalam masyarakat. Penyelesaian khalwat oleh Peradilan Adat maupun Qanun Syariat Islam pada tataran pelaksanaan oleh masyarakat adat sinkronisasi keduanya karena proses yang diselesaikan oleh Peradilan Adat itu adalah bagian dari ranahnya dan juga Qanun Syariat Islam juga ada ranahnya yang diselesaikan oleh Mahkamah Syar'iah. Orientasi akhirnya adalah pelaksanaan penyelesaian kasus khalwat antara Qanun Syariat Islam dengan Qanun Adat adalah sinkronisasi dengan aturan yang berlaku. Kata kunci: Harmonisasi, Implementasi dan Adat Istiadat.